Effective Direct Marketing for Eurotrans Logistik Indonesia in Surabaya - Levina Budiani (iBuss Management, 2020)
There is a high possibility for new business in any industry to be confronted by many challenges and obstacles. Eurotrans Logistik Indonesia is a local freight forwarding company which recently also opened its branch in Surabaya. Due to the lack of knowledge and experiences, the branch has the inability to attract new customers and as consequence has to suffer a massive financial loss. Therefore, this research aims to improve the sales and marketing strategy of Eurotrans Logistik Indonesia in Surabaya to reach the targeted number of sales and profit through effective direct marketing. This research focuses on qualitative research, with the use of quantitative research to support. The findings show that there are seven issues, in eliminating those issues, the branch has to improve both the direct marketing process and direct marketing personnel. Keyword: Direct Marketing, Freight Forwarding, Logistics